Silver Nanoparticles to Fight Candida Coinfection in the Oral Cavity - Monteiro, Douglas Roberto [UNESP]; Silva, Sónia; Negri, Melyssa; Gorup, Luiz Fernando; de Camargo, Emerson Rodrigues; Barbosa, Debora Barros [UNESP]; Henriques, Mariana (Elsevier, 2015)
This chapter is focused on the activity of silver nanoparticles (SN) as an antifungal agent against Candida albicans and Candida glabrata biofilms, which are involved in oral candidosis. A discussion focusing on the influence of the stabilizing agent, diameter of SN on its antibiofilm activity, influence of chemical stability of SN on Candida biofilms, the effect of SN against adhered cells and biofilms, the effect on extracellular matrix composition and structure of Candida biofilms, the combination of SN with conventional antifungal drugs, and the incorporation of SN into denture acrylic resin is incorporated in the present chapter. Because of the resistance of Candida biofilms to conventional drugs and the positive effect of SN against them, these nanoparticles can be used as an alternative antifungal agent.
Keywords: Biofilms; Candida albicans; Candida glabrata; Silver nanoparticles